Gaming und Bibliotheken - Deeg, Christoph (Praxiswissen, 2014)
Using a theoretical review as a foundation, this volume for the first time provides a comprehensive review of the manifold possibilities for the use of gaming in libraries. It presents new trends in gaming as well as current activities being conducted by libraries to reveal the growing impact of gaming on the transmission of culture and knowledge.